Jesus and the Jewish roots of the Virgin Mary: unveiling the Mother of the Messiah - Pitre, Brant James (Image, 2018)
Introduction. The problem with Mary -- The queen of heaven? -- Through ancient Jewish eyes -- The new Eve. The woman in Eden -- Mary the new Eve -- Immaculate Mary -- The new ark. The lost Ark of the Covenant -- Mary the new ark -- Assumed into heaven -- The queen mother. The queen mother in ancient Israel -- Mary the new queen -- Mother of "God with us" -- The perpetual virgin. Mary's Jewish vow -- The brothers of Jesus -- Ever-virgin -- The birth of the Messiah. The mother of the Messiah -- Mary's birth pangs -- Mary's womb and Jesus' tomb -- The new Rachel. Rachel in ancient Judaism -- Mary the new Rachel -- Mother of the church -- At the foot of the cross. Jesus' last words -- He took her to be his own -- Behold, your mother.